Highlighting the importance of cognitive engagement among sudents of higher learning institutions - Dzulkifli, Mariam Adawiah (IIUM Press, 2009)
Malaysian society puts great emphasis on levels of academic achievement. Parents are keen at seeing their children enrol in university and educational institutions are competing with each other to offer their best educational programme and be at the forefront of academic excellence. However, it is sad to note that a good level of academic achievement does not guarantee a good job in the market. Many recent graduates have difficulties in finding employment. It is reported that so many young people are facing problems in finding employment in Malaysia. Reports from business sector also indicate the low quality of graduates they receive from universities. These graduates according to them sometimes could not even comprehend the manual of an equipment, what m~re the way it works (Rosnani and Subailah, 2003). Employers nowadays feel that it is so hard to find employees who are not only knowledgeable but are well-equipped with thinking skills, the skills that are very much demanded in working sectors.